2017
DOI: 10.1371/journal.pone.0178042
|View full text |Cite
|
Sign up to set email alerts
|

Women's role in sanitation decision making in rural coastal Odisha, India

Abstract: BackgroundWhile women and girls face special risks from lack of access to sanitation facilities, their ability to participate and influence household-level sanitation is not well understood. This paper examines the association between women's decision-making autonomy and latrine construction in rural areas of Odisha, India.MethodsWe conducted a mixed-method study among rural households in Puri district. This included a cross sectional survey among 475 randomly selected households. These were classified as eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
93
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 28 publications
14
93
0
Order By: Relevance
“…It shows that as the age of the women increases, the level of their information seeking behviour decreases. These findings are in the agreement with the findings of the studies conducted by Routray Ramrao [3,8].…”
Section: Relationship Of Information Behaviour With Personal and Socisupporting
confidence: 93%
See 2 more Smart Citations
“…It shows that as the age of the women increases, the level of their information seeking behviour decreases. These findings are in the agreement with the findings of the studies conducted by Routray Ramrao [3,8].…”
Section: Relationship Of Information Behaviour With Personal and Socisupporting
confidence: 93%
“…behaviour included activities like identifying information needs, seeking information from various information sources and evaluating or checking information sources. On seeking behaviour, respondents were categorized into three categories; highly active, active and passive able 4 indicated that nearly half of the respondents (50%) were active seekers followed by 42 per cent of the respondents who had passive informationseeking behaviour and only 8 per cent respondents were highly active informationseekers for household health and hygiene One of the reasons for women's passive was that they lack confidence to take decisions independently, and were dependent on their spouse or other male family members for most decisions such as the The results were in line with the findings of the study of et al, (2017) [3].…”
Section: Behaviour Of Regarding Household Hygiene Practicessupporting
confidence: 85%
See 1 more Smart Citation
“…Considering the Gender Equality Index the African decision-makers need to concentrateand address some important obstacles that prevent African women from engaging on alevel playing field with men, and better focus its genderrelatedpolicy dialogue and interventions (African Development Bank Group, 2015). Routray, Parimita. (2017) examined the association between women's decision-making autonomy and latrine adoption in rural areas of Odisha and found that women's enjoy less freedom of making choice and decision with respect to installation of sanitation facility due to prevailing socio-cultural and economic constraints, and power hierarchies among household members (Routray, Parimita, 2017).Goel, Palaket., al conducted research study and concluded that there is need to educate women about how to livehealthy reproductive life using satisfactory absorbent material and its consequences during menstruation period as well as how to manage Menstrual Hygiene situation (Goel, Palak, et., al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Therefore, family decision making is in the hands of fishermen (Di Ciommo and Schiavetti, 2012; Mutikukuru- Maravanyika et al, 2016;Routray et al, 2017) in improving the household economy through empowerment (Nandi, 2015; Haque, 2016;Shakir, 2017;Agnihotri and Malipatil, 2018). Economic empowerment of coastal communities has an influence on the welfare of coastal communities (Rostin, 2016) through family income and household consumption expenditures (Michael, 2010).…”
mentioning
confidence: 99%